Recovery of ammonia from municipal wastewater through ion exchange - Aqilah Hani Binte Alfian (Nanyang Technological University, 2022)
The recovery of ammonia in wastewater treatment is important to ensure that the effluent discharge does not contribute detrimental effects to water bodies. Treatment methods such as ion exchange which is presently used in water softening can be effective in the removal of ammonia. Resins can vary from synthetic or natural zeolite to activated carbon such as biochar. In this study, the adsorption efficiency of chemically modified biochar in removing ammonia was investigated through batch kinetics and fixed-bed column adsorption tests. The optimum conditions were found to be pH 7.1 to 7.9 and a dosage 4 g/L. From the batch adsorption test, the pseudo second-order reaction corresponds the best with the equilibrium adsorption behavior of modified biochar, achieving qe of 3.83 mg/g. A range of contact time was investigated for the column adsorption test including 20, 25, 30 and 35 minutes in a lab-scale column. The column performed the best at EBCT of 35 min achieving a removal capacity of 3.26 mg/g. Further efforts should be carried out to investigate the use of modified biochar in industrial or trade wastewater effluent for other target pollutants. Additionally, the chemical modification of biochar using other acid and alkali solutions could be investigated as well.